2022
DOI: 10.1371/journal.pone.0264507
|View full text |Cite
|
Sign up to set email alerts
|

Reduced trolling on Russian holidays and daily US Presidential election odds

Abstract: Russian trolls generally supported the Trump campaign and were particularly active on Twitter 2015-2017. We find that trolling fell 35% on Russian holidays and to a lesser extent, when temperatures were cold in St. Petersburg. Exogenous variation in trolling by day allows us to consider indirectly-affected political behaviors in the US—outcomes that are less traceable via tweet sharing but potentially more important to policymakers than the direct dissemination previously studied. As a case in point, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…For example, Pruitt et al, (1988) found that differential media presentation of the same set of economic data, determined statistically significant differences in the accuracy of expectations regarding short-term future unemployment. Along the same lines, several political analysts have pointed out the key role played by Russian trolls, fake profiles and bot networks in diffusing misinformation that were crucial in influencing the vote that led to the Brexit, as well as to the election of the former American President Donald Trump, in 2016 (e.g., Almond et al, 2022). More recently, we have witnessed the rising of the no-vax movement during the COVID-19 pandemic, tremendously boosted by the diffusion of fake news through social networks like Facebook This preprint research paper has not been peer reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pruitt et al, (1988) found that differential media presentation of the same set of economic data, determined statistically significant differences in the accuracy of expectations regarding short-term future unemployment. Along the same lines, several political analysts have pointed out the key role played by Russian trolls, fake profiles and bot networks in diffusing misinformation that were crucial in influencing the vote that led to the Brexit, as well as to the election of the former American President Donald Trump, in 2016 (e.g., Almond et al, 2022). More recently, we have witnessed the rising of the no-vax movement during the COVID-19 pandemic, tremendously boosted by the diffusion of fake news through social networks like Facebook This preprint research paper has not been peer reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Survey results show the majority of the population uses social media as much or more compared to traditional media for news consumption, civic engagement, sharing opinions about social and political issues, and showing support or opposition for public policies (Thomas, 2015). Apart from hostility and polarization, harmful content in cyberspace raises several concerns, including religious hostility and intolerance (Mitts, 2019;Muller and Schwarz, 2020b), propaganda of violent and terrorist groups (Mitts et al, 2022), censorship and misinformation (Vicario et al, 2016;Azzimonti and Fernandes, 2022), political interference (Stella et al, 2018;Almond et al, 2022), and privacy and safety (Jain et al, 2021). Social media content could be a manifestation of underlying trends in polarization and hostility.…”
Section: Introductionmentioning
confidence: 99%